2019
DOI: 10.1002/jrsm.1337
|View full text |Cite
|
Sign up to set email alerts
|

Conducting gene set tests in meta‐analyses of transcriptome expression data

Abstract: Research synthesis, eg, by meta‐analysis, is more and more considered in the area of high‐dimensional data from molecular research such as gene and protein expression data, especially because most studies and experiments are performed with very small sample sizes. In contrast to most clinical and epidemiological trials, raw data are often available for high‐dimensional expression data. Therefore, direct data merging followed by a joint analysis of selected studies can be an alternative to meta‐analysis by P va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…With the increasing availability of large collections of omic data, the reproducibility of machine learning prediction models has raised great concerns when conducting cross-study predictions with the impact of study heterogeneity. Previous studies have addressed this issue and developed many statistical methods to overcome study heterogeneity, including merging with batch effect removal [ 36 ] and ensemble learning methods [ 9 ]. In this study, we performed a comprehensive analysis of different methods on the phenotype prediction by integrating heterogeneous omic studies.…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing availability of large collections of omic data, the reproducibility of machine learning prediction models has raised great concerns when conducting cross-study predictions with the impact of study heterogeneity. Previous studies have addressed this issue and developed many statistical methods to overcome study heterogeneity, including merging with batch effect removal [ 36 ] and ensemble learning methods [ 9 ]. In this study, we performed a comprehensive analysis of different methods on the phenotype prediction by integrating heterogeneous omic studies.…”
Section: Discussionmentioning
confidence: 99%
“…Similar approach has also been taken by Shen and coworkers (Shen et al 2017 ), who combined microarray abiotic stress datasets and successfully identified common and specific gene modules to different abiotic stresses. Such comparative transcriptomic analyses have several advantages over conventional meta-analysis studies, which normally analyzed the DEGs from different studies separately and compared the gene lists at the end, especially in terms of higher sensitivity of detecting differentially expressed gene sets enrichment (Kosch and Jung 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing availability of large collections of omic data, the reproducibility of machine learning prediction models has raised great concerns when conducting cross-study predictions with the impact of study heterogeneity. Previous studies have addressed this issue and developed many statistical methods to overcome study heterogeneity, including merging with batch effect removal [37] and ensemble learning methods [9]. In this study, we performed a comprehensive analysis of different methods on the phenotype prediction by integrating heterogeneous omic studies.…”
Section: Discussionmentioning
confidence: 99%